SETTLEMENT OF DISPUTES BETWEEN ELECTRICITY CONSUMER CUSTOMERS AND PLN IN PAYMENT OF ELECTRICITY BILL FINES - Kemas Abdul Gaffur; Anwar Budiman; Abdul Chair Ramadhan (International Peneliti Ekonomi, Sosial dan Teknologi, 2023)
This study aims to determine the validity of the Decree of the Board of Directors of PLN Number 1486.K/Dir/2011, dated December 27, 2011, concerning the Ordering of Electricity Usage (P2TL), both according to positive law and based on the dogmatics of legal science. Normative legal research focuses on solving legal problems through unique mechanisms, examining the law as a system of rules. This research does not conduct field research and is understood as a science of rules, focusing on dogmatics and legal systems. Existing research data is collected through literature studies, including literature materials in the form of primary materials or sources. The result of the case between Pioneer Chemical and PT PLN (Persero) Distribution of Greater Jakarta and Tangerang Area Cengkareng revolves around the Decree of the Board of Directors of PT PLN (Persero) No. 1486.K/Dir/2011, which states that the calculation of supplementary bills and the proposal for P2TL settlement are based on administrative and/or laboratory examinations. The Panel of Judges decided that the calculation of supplementary bills did not need to be guided by laboratory results, and the Defendant had the authority to conduct P2TL as outlined in the Decree. The decree met the criteria of legitimacy, interpretation, sanction, and jurisdiction in the legal system approach. Pioneer Chemical, as the plaintiff, was unable to submit evidence of unlawful acts committed by PT PLN (Persero) Distribution of Greater Jakarta and Tangerang Area Cengkareng.